Seismic Resistant Design of Structures in the Low to Medium Seismicity Countries: Flexible Structures for Economic Construction - Zaini Sooria, Sherliza Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Earthquake hazard mitigation aims to reduce the impact of future earthquake disasters. It is proposed to adopt the use of flexible structures in seismic resistant design for Malaysia. In this study pushover analysis is performed on a bridge structure to illustrate how flexible structures fulfil the performance objectives of surviving an earthquake, and help keep the construction cost of seismic resistant structures at a reasonable level. Two types of cross section of the Samudera Bridge are subjected to monotonically increasing lateral forces until a target displacement is reached. First, pushover analysis on the original cross section is performed as a control to observe the seismic performance of the structure at the site. Next, pushover analysis is performed on the modified cross section, which represents the flexible structure, to study its seismic performance and the economic impact of introducing flexible structures as an approach to control the construction cost of seismic resistant structures. The study seems to show that desired ductility for satisfactory seismic performance may be achieved by using flexible structures, and at the same time the increase in the construction cost of flexible structures is reasonably low and acceptable by the industry.